2007
DOI: 10.1183/09031936.00005107
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent tuberculosis from 1992 to 2004 in a metropolitan area

Abstract: The proportion of recurrent tuberculosis (TB) cases caused by re-infection has varied widely in previous studies. The aim of the present study was to determine the relative frequency of relapse and exogenous re-infection in patients with second episodes of TB, using DNA fingerprinting.A population-based retrospective longitudinal descriptive study was conducted in Madrid (Spain) during 1992-2004. The study consisted of 645 patients with culture-confirmed TB. Of these, 20 (3.1%) were retained because they prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
49
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 23 publications
6
49
2
1
Order By: Relevance
“…Immigrants usually come from countries with a higher prevalence of TB than Spain; therefore, exogenous re-infection is less likely in Spain than in their respective home countries [25]. Besides that, many of the IVDUs may have died, reducing the pool of IVDUs who could have either exogenous or endogenous TB infection.…”
Section: Tuberculosis and Hiv In Immigrants In Spain 231mentioning
confidence: 99%
“…Immigrants usually come from countries with a higher prevalence of TB than Spain; therefore, exogenous re-infection is less likely in Spain than in their respective home countries [25]. Besides that, many of the IVDUs may have died, reducing the pool of IVDUs who could have either exogenous or endogenous TB infection.…”
Section: Tuberculosis and Hiv In Immigrants In Spain 231mentioning
confidence: 99%
“…Of the factors determined to be predictive of tuberculosis recurrence, HIV-infection and immune-suppression have been previously identified in countries of high and low TB incidence where most recurrences after successful TB treatment are due to endogenous reactivation (10,11). In fact, the physiological immune responses of circulating leukocytes to various stressful events are characterized by an increased neutrophil count and decreased lymphocyte count (12).…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] In areas of low TB incidence, relapse is usually due to endogenous reactivation. [15][16][17] In areas of high TB incidence, however, the incidence of relapse attributed to re-infection can reach 75%. 12,18,19 Yemen is a low TB incidence country, with an estimated rate of 25 cases/ 100 000.…”
Section: Discussionmentioning
confidence: 99%
“…17,23,27 The association between cavitation and relapse could be attributed to poor drug penetration into the devascularised cavities or the surrounding fi brotic tissue. 27 Our study shows that weight gain is strongly associated with TB relapse, supporting the fi ndings of Khan et al 28 However, weight loss was also significantly associated with increased risk for relapse, corroborating the fi ndings of Benator et al 27 The positive association between diabetes and TB has been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation